2016
DOI: 10.1177/0003319716672526
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Intima–Media Thickness Predicts Major Cardiovascular Events During 7-Year Follow-Up in 64-Year-Old Women Irrespective of Other Glucometabolic Factors

Abstract: Cardiovascular (CV) disease (CVD) is a leading cause of morbidity and mortality worldwide. Most CV events are caused by atherosclerosis. Diabetes and impaired glucose tolerance are associated with greater carotid intima-media thickness (IMT) and increased risk for CVD. The present study examined if common carotid artery IMT (CCAIMT) is predictive of CVD irrespective of glucose tolerance category and glycated hemoglobin (HbA1c) in a sample of 639 women with different glucose tolerance categories. During 7-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…A systematic review and meta-analysis concluded that carotid intima-media thickness is a strong independent predictor of future vascular events, although data for younger individuals are limited[89]. A prospective cohort study of women shows that increased carotid intima-media thickness predicts cardiovascular events during 7-year follow-up regardless of glucose tolerance and other cardiovascular risk factors[90]. In a systematic review, population groups with cardiovascular disease had a higher carotid intima-media thickness compared to population groups free of cardiovascular disease[55].…”
Section: Subclinical Vascular Disease Associated With Insulin Resistamentioning
confidence: 99%
“…A systematic review and meta-analysis concluded that carotid intima-media thickness is a strong independent predictor of future vascular events, although data for younger individuals are limited[89]. A prospective cohort study of women shows that increased carotid intima-media thickness predicts cardiovascular events during 7-year follow-up regardless of glucose tolerance and other cardiovascular risk factors[90]. In a systematic review, population groups with cardiovascular disease had a higher carotid intima-media thickness compared to population groups free of cardiovascular disease[55].…”
Section: Subclinical Vascular Disease Associated With Insulin Resistamentioning
confidence: 99%
“…[7][8][9][10][11] Carotid artery stenosis, plaques, and carotid intima-media thickness (cIMT) detected by B-mode ultrasonography were found to be reliable markers for future CVD in middle-aged and elderly populations. 9,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, most studies were from Europe, the United States, or South Korea. Although several recent prospective cohort studies have reported the associations of CAS and CVD in China, less attention has been paid to this association in older adults.…”
Section: Introductionmentioning
confidence: 99%